The effect of livestock manures on growth and nutritive values of Eisenia foetida - Khairudin, Fitri Amirul (2015)
A study (5 weeks duration) was conducted to evaluate the efficiency of an exotic earthworm species (Eisenia foetida) for decomposition of four different types of organic materials ; peat soil as control,goat manures,cow manures and mixtures of goat and cow manures into valuable vermicompost . Each treatment group consisted of three replicates and worm vermicasts and earthworm were examined after 5 weeks . The percentage of nitrogen, phosphorous and potassium in vermicompost was significantly increase (p<0.05) while pH and total organic carbon declined as a function of the vermicomposting period . The final percentage gains in vermicasts of total nitrogen and phosphorus in cow manure vermicasts were higher than those in control and goat manure. Cow vermicasts had a higher N content than goat vermicasts and also the C:N ratio of fresh materials was higher than that of vermicasts for all treatment . There was a shift from the initial neutral pH condition towards an acidic condition due to the bioconversion of the organic material into various intermediate types of organic acid . Earthworm biomass weight gains showned no significant difference when compared to control although increase in all treatment . Earthworm biomass and dry matter (DM) of Eisenia foetida cultured in cow manure were higher than in goat manure , followed by mixture manures and peatsoil ( control ). In conclusion, cow manure provided a more nutritious and friendly environment to the earthworms than peatsoil ,goat manure and mixture of manures . The hypothesis is accecpted .The data reveals that vermicomposting (using Eisenia foetida) is a suitable technology for the decomposition of different types of organic wastes (domestic as well as industrial) into value-added material .